ANALISIS DAYA SAING INDUSTRI MANUFAKTUR (IM) DI KABUPATEN OGAN KOMERING ULU (OKU) SELATAN - Pandriadi, Pandriadi; Amah, Mas; Mario, Asma (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
Abstract Manufacturing Industry (IM) is a part of economy elevator in OKU Selatan District. Unfortunaltely, the contribution of this sector, particularly to PDB is still low. This research aims to analize the competitiveness of IM in OKUS District by using Location Quotient (LQ) and SWOT Analysis. LQ analysis tried to compare the number of PDRB between OKUS District and South Sumatera Province. The result shows that the number of LQ are below 1. This means that IM in OKUS District still have low competitiveness. By using SWOT Analysis, it is in third quadrant. It means that actually IM have large oportinities to be developed but it also has high challenge. In addition, according to Wheelen Matrix, IM of OKUS District is in cel 8 (growth). The implication of this cel are IM need to focus on one product (specialization) or develop to many products (diversification). Key Words: Competitiveness, Manufacturing Industry, Location Quotient, SWOT